Reader's satisfaction and purchase probability of Melaka Hari Ini newspaper / Hamidah Norman, Suhailah Ibrahim and Noor Azima Mohammad (Faculty of Business and Management, 2007)
This research would ascertain reader's satisfaction of product, promotion and purchase probability for a newspaper Melaka Hari Ini (MHI). The Malaysian newspaper industry has been around since 1800's and gone through changes to suit the demands from readers of various age groups (mostly of 15 to 34 years old representing 53% of readership - Source: World Association of Newspaper, 2004). Readers can choose to buy newspapers that are available in two fonnats - broadsheet and tabloid (half the size of broadsheet) and sold at RMI to RMl.50 per copy. Another alternative is through online by surfing the newspapers websites'. In view of this, management of Melaka Hari Ini must reciprocate via the adaptation of their marketing mix to upkeep themselves with rapid changes.